2012
DOI: 10.1111/j.1537-2995.2012.03915.x
|View full text |Cite
|
Sign up to set email alerts
|

African culturally and linguistically diverse communities’ blood donation intentions in Australia: integrating knowledge into the theory of planned behavior

Abstract: The TPB applies differently when examining African CALD communities' blood donation intentions in Australia. Knowledge is an important mediating component of the Extended TPB model rather than directly affecting intentions. Addressing CALD communities' psychographic characteristics may assist blood services in developing targeted strategies to increase donations within these communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
(207 reference statements)
4
25
0
Order By: Relevance
“…It specifically shows that political knowledge is rather subsidiary compared with perceived behavioural control (Ajzen et al, 2011), meaning that internal political efficacy is more important in the prediction of political behaviour. Adding to that, political knowledge affected political participation through internal political efficacy, and it primarily affected behavioural intentions (compare also Dalrymple et al, 2013; Polonsky et al, 2013). Although accurate political knowledge may not always be necessary, nor is it sufficient, to predict behaviour (Ajzen et al, 2011), it contributes to decisions that conform with an individual’s preferences and political attitudes (Galston, 2001), at least indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It specifically shows that political knowledge is rather subsidiary compared with perceived behavioural control (Ajzen et al, 2011), meaning that internal political efficacy is more important in the prediction of political behaviour. Adding to that, political knowledge affected political participation through internal political efficacy, and it primarily affected behavioural intentions (compare also Dalrymple et al, 2013; Polonsky et al, 2013). Although accurate political knowledge may not always be necessary, nor is it sufficient, to predict behaviour (Ajzen et al, 2011), it contributes to decisions that conform with an individual’s preferences and political attitudes (Galston, 2001), at least indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Although accurate political knowledge may not always be necessary, nor is it sufficient, to predict behaviour (Ajzen et al, 2011), it contributes to decisions that conform with an individual’s preferences and political attitudes (Galston, 2001), at least indirectly. Also, it is a precursor of more proximal beliefs and personal preferences that closely relate to actual participation (e.g., Polonsky et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of knowledge can result in unreasonable fears regarding the donation of blood. Also, if the minority group has its own language, language barriers can arise and hinder blood donations of these potential donors (Polonsky et al 2013) especially as it was also found regarding volunteering for mainstream organizations of Asian immigrants in the United States (Lee and Moon 2011). With increasing assimilation to the new country, the lack of knowledge and language barriers could diminish, however, some groups, especially in big cities, live in subcultures that allow them to work, live, and communicate in their own language.…”
Section: Factors For Low Minority Participationmentioning
confidence: 99%
“…the belief in control over performing the behaviour) and self‐efficacy (i.e. the belief in behavioural capabilities) is debated , in the blood donation literature, self‐efficacy has typically been assessed in addition to or, most frequently, in place of PBC .…”
Section: What Do We Know?mentioning
confidence: 99%